Soil loss and runoff characteristics in response to varying underground fissure ratios on karst slopes with thin soil layers in Southwest China - Tianyang Li; Yunfei Bi; Lan Song; Binghui He (Journal of Hydrology: Regional Studies)
Study region: Karst slopes with thin soil layers, southwest China. Study focus: Bedrock fissures can reallocate runoff and soil losses on karst slopes. However, the response of soil loss and runoff characteristics to bedrock surface fissure to the bedrock surface area ratio (RUF) on karst slopes with thin soil layers remain unclear. This study assesses the runoff and soil loss characteristics on karst slopes with a thin soil layer under five RUF scenarios (0, 1, 2, 3, and 4 %), a single rainfall intensity of 1.0 mm min−1, and three slope gradients (10°, 15°, and 20°) through laboratory simulations. New hydrological insight for the region: The highest surface runoff rate was observed under the 0 % RUF scenario at all slopes. Whereas the highest fissure runoff rate was found under the 4 % RUF scenario at the 15° slope. In contrast, the highest surface soil loss rates were found under the 1, 2, and 0 % RUF scenarios at the 10°, 15°, and 20° slope, respectively. The 2 % RUF scenario exhibited a significantly higher underground soil leakage loss rate at the 10° slope than that under other simulation scenarios. The surface runoff-to-total runoff and surface soil loss-to-total soil loss ratios under different scenarios ranged from 45.4 % to 78.3 % and 86.5–96 %, respectively. These results underscore that RUF redirects runoff, thereby modifying surface soil and leakage losses on karst slopes.